2019
DOI: 10.34115/basrv3n5-010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização física e química de clones de ariá (Calathea allouia)

Abstract: Caracterização física e química de clones de ariá (Calathea allouia) Characterization physical and chemical of clones ariá (Calathea allouia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
(3 reference statements)
3
6
1
Order By: Relevance
“…Regarding the mineral content present in C. allouia tubers, potassium is the major mineral and represents more than 95% of mineral fraction, followed by calcium (2.7%) and magnesium (1.9%). These results were similar to those reported in other research for C. allouia (Marques et al, 2019; Teixeira et al, 2016). A similar mineral profile was also observed for other tubers, such as sweet potato (Kourouma et al, 2019) and cassava (Charles et al, 2005).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Regarding the mineral content present in C. allouia tubers, potassium is the major mineral and represents more than 95% of mineral fraction, followed by calcium (2.7%) and magnesium (1.9%). These results were similar to those reported in other research for C. allouia (Marques et al, 2019; Teixeira et al, 2016). A similar mineral profile was also observed for other tubers, such as sweet potato (Kourouma et al, 2019) and cassava (Charles et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…The crude protein content was within the range observed (0.53%–1.07%) by Marques et al (2019), in clones of C. allouia , but much lower than the value observed (4.55%) by Minh (2018). Although the crude protein content in C. allouia tubers was low, Martin and Cabanillas (1976) reported that the amino acid profile of this tuber is balanced, with 18 types of amino acids, with glutamic acid being the major one followed by aspartic acid and leucine.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations